10 years of denosumab treatment in postmenopausal women with osteoporosis: results from the phase 3 randomised FREEDOM trial and open-label extension. Issue 7 (July 2017) - Bone, Henry G; Wagman, Rachel B; Brandi, Maria L; Brown, Jacques P; Chapurlat, Roland; Cummings, Steven R; Czerwiński, Edward; Fahrleitner-Pammer, Astrid; Kendler, David L; Lippuner, Kurt; Reginster, Jean-Yves; Roux, Christian; et al.
Summary: Background: Long-term safety and efficacy of osteoporosis treatment are important because of the chronic nature of the disease. We aimed to assess the long-term safety and efficacy of denosumab, which is widely used for the treatment of postmenopausal women with osteoporosis. Methods: In the multicentre, randomised, double-blind, placebo-controlled, phase 3 FREEDOM trial, postmenopausal women aged 60–90 years with osteoporosis were enrolled in 214 centres in North America, Europe, Latin America, and Australasia and were randomly assigned (1:1) to receive 60 mg subcutaneous denosumab or placebo every 6 months for 3 years. All participants who completed the FREEDOM trial without discontinuing treatment or missing more than one dose of investigational product were eligible to enrol in the open-label, 7-year extension, in which all participants received denosumab. The data represent up to 10 years of denosumab exposure for women who received 3 years of denosumab in FREEDOM and continued in the extension (long-term group), and up to 7 years for women who received 3 years of placebo and transitioned to denosumab in the extension (crossover group). The primary outcome was safety monitoring, comprising assessments of adverse event incidence and serious adverse event incidence, changes in safety laboratory analytes (ie, serum chemistry and haematology), and participant incidence of denosumab antibody formation. Secondary outcomes included new vertebral, hip, and non-vertebral fractures as well as bone mineral density (BMD) at the lumbar spine, total hip, femoral neck, and one-third radius. Analyses were done according to the randomised FREEDOM treatment assignments. All participants who received at least one dose of investigational product in FREEDOM or the extension were included in the combined safety analyses. All participants who enrolled in the extension with observed data were included in the efficacy analyses. The FREEDOM trial (NCT00089791 ) and its extension (NCT00523341 ) are both registered with ClinicalTrials.gov . Findings: Between Aug 3, 2004, and June 1, 2005, 7808 women were enrolled in the FREEDOM study. 5928 (76%) women were eligible for enrolment in the extension, and of these, 4550 (77%) were enrolled (2343 long-term, 2207 crossover) between Aug 7, 2007, and June 20, 2008. 2626 women (1343 long-term; 1283 crossover) completed the extension. The yearly exposure-adjusted participant incidence of adverse events for all individuals receiving denosumab decreased from 165·3 to 95·9 per 100 participant-years over the course of 10 years. Serious adverse event rates were generally stable over time, varying between 11·5 and 14·4 per 100 participant-years. One atypical femoral fracture occurred in each group during the extension. Seven cases of osteonecrosis of the jaw were reported in the long-term group and six cases in the crossover group. The yearly incidence of new vertebral fractures (ranging from 0·90% to 1·86%) and non-vertebral fractures (ranging from 0·84% to 2·55%) remained low during the extension, similar to rates observed in the denosumab group during the first three years of the FREEDOM study, and lower than rates projected for a virtual long-term placebo cohort. In the long-term group, BMD increased from FREEDOM baseline by 21·7% at the lumbar spine, 9·2% at total hip, 9·0% at femoral neck, and 2·7% at the one-third radius. In the crossover group, BMD increased from extension baseline by 16·5% at the lumbar spine, 7·4% at total hip, 7·1% at femoral neck, and 2·3% at one-third radius. Interpretation: Denosumab treatment for up to 10 years was associated with low rates of adverse events, low fracture incidence compared with that observed during the original trial, and continued increases in BMD without plateau. Funding: Amgen.